Optimalisasi Jaringan Transportasi Logistik memakai Metode Minimum Spanning Tree dengan POM–QM dan MATLAB - Daniel Satya Kusuma (Universitas Katolik Indonesia Atma Jaya, 2024)
In its operations, PT Saudara Sukses Abadi is a service company that operates in the logistics sector or tracking company. In the company's operational activities, there are often several orders that come in regularly and need to be delivered to certain target areas with various location objectives. Often companies combine cargo from several orders so that container trucks can load several travel orders for varied destination locations without reference to travel considerations so that the distance traveled by container trucks is less efficient and effective. Based on these problems, the suggestion or input that can be considered is to create a network between locations and mapping the location of the optimal delivery range network for the company by considering the distance between locations or destination points to be traversed in ongoing operations. The approach or optimization method used is the Minimum Spanning Tree method to cover the location of the entire network area that is the company's travel destination with consideration of the closest mileage. In carrying out this optimization, POM - QM application assistance and Matlab software are used to support data processing in terms of accuracy, to visual depiction so that it can be input or consideration for companies in carrying out shipping operations and logistics trips. Keywords/Kata kunci: Network, Optimization, Minimum Spanning Tree